Localized cutaneous acremoniasis in a patient with hyperimmunoglobulin E syndrome. - Tambe, S.A.; Jerajani, H.R.; Ghate, S.S.; Lambay, S.A. (European Journal of Pediatric Dermatology, 2011)
Hyperimmunoglobulin E syndrome is a primary immunodeficiency characterized by elevated levels of IgE, recurrent infections and skin, skeletal and dental alterations linked to a deficiency of T lymphocytes. The Acremonium is a saprophytic fungus responsible for serious infections in immunocompromised subjects. We report in this paper a condition never published in the past, acremoniasis in a child with hyperimmunoglobulin E syndrome.